Electrochemical synthesis of carbon nano onions. Issue 22 (9th October 2020) - Bian, Yixuan; Liu, Lu; Liu, Di; Zhu, Zhiwei; Shao, Yuanhua; Li, Meixian
Abstract : Electrochemical synthesis of hollow and solid carbon nano onions from simple aromatic compounds in acetonitrile on a platinum plate electrode by a multi-potential steps method. Abstract : As an important class of carbon nanomaterials, carbon nano onions (CNOs) have attracted considerable interest in recent years due to their unique structures and properties. In this work, the electrochemical synthesis of CNOs (including hollow carbon nano onions (H-CNOs) and solid carbon nano onions (S-CNOs)) was achieved from simple aromatic compounds in acetonitrile on a platinum plate electrode by a multi-potential steps method. The electrolytic products on the platinum plate electrode were separated to obtain H-CNOs and S-CNOs by heating treatment, followed by ultrasonic and gradient centrifugation. The reaction mechanism was presumed to be involved with dehydrogenation oxidation and reductive dimerization, as well as cross-linking reactions. The obtained H-CNOs and S-CNOs were characterized by scanning electron microscopy, transmission electron microscopy and Raman spectroscopy. This work has provided a new approach to synthesize and separate S-CNOs and H-CNOs. The developed method does not require sophisticated equipment or high energy consumption. The obtained CNOs would be applicable to construct electrocatalysis and sensing interfaces.